Names and Surnames of Citizens of the Republic of Lithuania with the Letters X, W and Q: Argumentum Pro and Contra - Murinienė, Lina (Taikomoji kalbotyra, 2025)
Until 2022, the names and surnames of persons of non-Lithuanian nationality in the passport of a citizen of the Republic of Lithuania were written in Lithuanian characters. The original form, written in Latin characters, including the letters x, w and q, could be retained by citizens of another state. According to a new law adopted by the Seimas of the Republic of Lithuania in 2022, in certain cases, the names and surnames of citizens of the Republic of Lithuania and their children may be written in Latin characters, including x, w and q, without diacritical marks. There were heated discussions on the so-called issue of the three letters in the media. The study aims to reveal the diversity of views on the Seimas‘ decision and clarify the arguments used to evaluate the law mentioned earlier favourably or unfavourably. The research material is 16 in-depth semi-structured interviews. Respondents are users of social networks, mostly Facebook; all of them are of Lithuanian nationality. A rhetorical communication scheme was used to conduct qualitative content analysis typical of informative argumentative texts. The argumentation research scheme presented by Frans H. van Eemeren and Robert Grootendorst was partly followed, focusing mostly on the main statements and arguments. The work was carried out by identifying logical topic. The research revealed a fairly broad assessment of the law adopted by the Seimas – from very unfavourable to highly supportive. Most of the arguments of the opposing sides are based on the same logical topic: the alphabet, the ability to read, language norms, relations with Poland, integration and self-integration of national minorities, and individual rights. The argumentation of those who disagree with the Seimas decision, in addition to the already mentioned topics common to both sides, encompass the issue of national identity and criticism of the government (attitudes towards the state language and laws). Both sides rely not only on linguistic but also on legal, social, political, geopolitical, and ideological arguments. Based on the insights of the respondents who evaluated this Seimas decision favourably, we could speak about the emotional arguments, characteristic of the opposing side, which have psychological and traumatic aspects associated with polonophobia. The research was conducted from 2020 to 2023 as part of the “Connective digital memory in borderlands: A mixed-methods study of cultural identity, heritage communication and digital curation on social networks” project.